Chemical ZE isomer switching of arylazopyrazoles using acid - Gibson,R; Calbo,J; Fuchter,MJ (ChemPhotoChem, 2019)
Arylazopyrazoles show significant potential as nextgeneration photoswitches, in particular because of the high thermal stability of their Zisomers. Herein we investigate the potential to perform Z−Eisomer chemical switching of arylazopyrazoles using acid. We show that acidaccelerated isomerisation allows for robust Z−E switching using mild acids and opens up the possibility to use lightacid cycles to near quantitatively and reversibly switch the arylazopyrazoles at room temperature. We attribute the chemical switching to azonium formation, facilitated by mesomeric stabilisation by the pyrazole ring. Coupled with their exceptionally long Zisomer halflives, we believe our study may open up a wider array of functional opportunities for the arylazopyrazoles.